Establishing the impact of powerful AGN on their host galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Harrison, C. M.; Molyneux, S. J.; Scholtz, J.; Jarvis, M. E.
Abstract: Establishing the role of active galactic nuclei (AGN) during the formation of galaxies remains one of the greatest challenges of galaxy formation theory. Towards addressing this, we summarise our recent work investigating: (1) the physical drivers of ionised outflows and (2) observational signatures of the impact by jets/outflows on star formation and molecular gas content in AGN host galaxies. We confirm a connection between radio emission and extreme ionised gas kinematics in AGN hosts. Emission-line selected AGN are significantly more likely to exhibit ionised outflows (as traced by the [O iii] emission line) if the projected linear extent of the radio emission is confined within the spectroscopic aperture. Follow-up high resolution radio observations and integral field spectroscopy of 10 luminous Type 2 AGN reveal moderate power, young (or frustrated) jets interacting with the interstellar medium. We find that these sources live in highly star forming and gas rich galaxies. Additionally, by combining ALMA-derived dust maps with integral field spectroscopy for eight host galaxies of z ≈ 2 X-ray AGN, we show that Hα emission is an unreliable tracer of star formation. For the five targets with ionised outflows we find no dramatic in-situ shut down of the star formation. Across both of these studies we find that if these AGN do have a negative impact upon their host galaxies, it must be happening on small (unresolved) spatial scales and/or an observable galaxy-wide impact has yet to occur.